Extending SSIS with .NET Scripting A Toolkit for SQL Server Integration Services - van Rossum, Joost; Baccaro, Regis (Apress : Imprint: Apress, 2015)
Extending SSIS with .NET Scripting is a timeless and comprehensive scripting toolkit for SQL Server Integration Services to solve a wide array of everyday problems that SSIS developers encounter. The detailed explanation of the Script Task and Script Component foundations helps you develop your own scripting solutions, but this book also shows a broad arsenal of readymade and well-documented scripting solutions for common problems. All examples are in both C# and VB.NET, and work for all current versions of SSIS. SSIS is one of the leading ETL, Data Consolidation, and Data Transformation tools in today's market. SSIS is used by ETL Developers, DBAs and Data Analysts to transform data as required for different ETL processes. There are many built-in components and tasks to help developers to perform actions. For example, there are tasks for sending and receiving files through FTP, sending an email, and for accessing a wide range of database management systems. Yet there are times when developers require a task or component that does not exist and it would make their life much easier if they could create that task or component, and that is what this book it is about. It shows how to write .NET scripts and use the powerful Microsoft .NET library to implement new functionality as needed. Provides a timeless scripting toolkit for all current SSIS versions Gives a comprehensive explanation of scripting in SSIS Offers a wide array of readymade examples for everyday problems.